2018
DOI: 10.1128/jvi.01273-18
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Spliced Protein (HBSP) Suppresses Fas-Mediated Hepatocyte Apoptosis via Activation of PI3K/Akt Signaling

Abstract: Hepatitis B spliced protein (HBSP) is known to associate with viral persistence and pathogenesis; however, its biological and clinical significance remains poorly defined. Acquired resistance to Fas-mediated apoptosis is thought to be one of the major promotors for hepatitis B virus (HBV) chronicity and malignancy. The purpose of this study was to investigate whether HBSP could protect hepatocytes against Fas-initiated apoptosis. We showed here that HBSP mediated resistance of hepatoma cells or primary human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…These viruses utilize signaling pathways such as ERK, RSK, PI3K, Rho, and Rac1 GTPases for cell cycle progression, viral entry, cellular transformation, expression of viral genes, and the establishment of infection. HIV [270], HCV [271,272], HBV [273][274][275], EBV, and KSHV [276][277][278][279] exploit host AKT, PI3K, mTOR signaling pathways for the evasion of apoptosis, infected cell survival, and proliferation, viral replication, production, vesicle formation, intracellular motility and activation of transcription factors. HIV [280], HCV [281], HBV [282], EBV [283], and KSHV [269] utilize myosin/kinesin for viral transmission, virion transcytosis, virus entry, intracellular viral transport, and formation of highly metastatic and invasive tumors with the leading edge.…”
Section: Hh Signaling Pathways During Infections and Viral Malignanciesmentioning
confidence: 99%
“…These viruses utilize signaling pathways such as ERK, RSK, PI3K, Rho, and Rac1 GTPases for cell cycle progression, viral entry, cellular transformation, expression of viral genes, and the establishment of infection. HIV [270], HCV [271,272], HBV [273][274][275], EBV, and KSHV [276][277][278][279] exploit host AKT, PI3K, mTOR signaling pathways for the evasion of apoptosis, infected cell survival, and proliferation, viral replication, production, vesicle formation, intracellular motility and activation of transcription factors. HIV [280], HCV [281], HBV [282], EBV [283], and KSHV [269] utilize myosin/kinesin for viral transmission, virion transcytosis, virus entry, intracellular viral transport, and formation of highly metastatic and invasive tumors with the leading edge.…”
Section: Hh Signaling Pathways During Infections and Viral Malignanciesmentioning
confidence: 99%
“…After the virus or its genome gets inside the infected cell, ssRNA+ viruses and other enveloped ones that replicate in the cytoplasm manage the cell metabolism to develop the replication scaffold, this membrane structure bolstering the so-called ‘virus factory’ [ 5 , 58 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. There is consensus on that the functions of these structures are (i) to compartmentalize the diverse processes involved in viral genome replication, its envelopment, and structural protein assembly; (ii) to increase virion concentration during budding before infecting naïve cells; and (iii) to create a protected environment to escape the innate immune recognition of the viral components.…”
Section: Lipid Regulation In Virus Replication: Viral Factoriesmentioning
confidence: 99%
“…Liu et al indicated that HBSP is as a new derivative of EPO for tissue protection, as it has a good protective effect on the body from myocardial ischemia . According to Wu Set al, HBSP inhibits hepatocyte apoptosis through PI3K/Akt pathway, suggesting that the intervention of inhibiting Akt activation or functional activity may have therapeutic value during the process. PI3K/Akt pathway was reported to be involved in tissue injuries, such as I/R‐induced renal injury, streptozotocin‐induced testicular injury and trioxide‐induced liver injury .…”
Section: Discussionmentioning
confidence: 99%